2007
DOI: 10.2319/101906-430.1
|View full text |Cite
|
Sign up to set email alerts
|

Third-Molar Development in Relation to Chronologic Age in Turkish Children and Young Adults

Abstract: The use of third molars as a developmental marker is appropriate, especially when comparing the obtained standard deviation with other skeletal age calculation techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
108
3
40

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(173 citation statements)
references
References 25 publications
22
108
3
40
Order By: Relevance
“…The order of frequency for M3 agenesis in this study is incompatible with the reports published by those authors. 13,23,24 In agreement with a recently published paper, 4 the order of the frequency for M3 agenesis was found to be one, two, four, and three M3s. Furthermore, Kazanci et al, 5 Daito et al, 8 Mok and Ho, 12 and Sandhu and Kaur 25 reported that M3 agenesis was observed with a higher frequency in the maxilla; this was in agreement with our results.…”
Section: Patterns Of Third-molar Agenesissupporting
confidence: 79%
See 1 more Smart Citation
“…The order of frequency for M3 agenesis in this study is incompatible with the reports published by those authors. 13,23,24 In agreement with a recently published paper, 4 the order of the frequency for M3 agenesis was found to be one, two, four, and three M3s. Furthermore, Kazanci et al, 5 Daito et al, 8 Mok and Ho, 12 and Sandhu and Kaur 25 reported that M3 agenesis was observed with a higher frequency in the maxilla; this was in agreement with our results.…”
Section: Patterns Of Third-molar Agenesissupporting
confidence: 79%
“…On the other hand, according to some studies, 23,24 the order of frequency for the M3 agenesis is one, two, three, and four M3s. The order of frequency for M3 agenesis in this study is incompatible with the reports published by those authors.…”
Section: Patterns Of Third-molar Agenesismentioning
confidence: 99%
“…Diagnostic accuracy of M3 to predict age 18 was tested. Design Methods were tested on a target sample of 300 dental panoramic radiographs (age [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Diagnostic accuracy was assessed on separate reference data (n = 1,663, age [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Souvent, son éruption n'est pas complète, soit par manque de place sur l'arcade, soit à cause d'un mauvais axe d'éruption. Ce n'est que vers 4 ou 5 ans qu'apparaît le germe de la troisième molaire avec une avance des dents maxillaires sur les dents mandibulaires [20], le début de la calcification intervient entre 8 et 11 ans [21,22] et l'achèvement de la couronne entre 12 et 15 ans. Le mouvement ascensionnel de la dent débute alors et elle redresse son axe.…”
Section: Discussionunclassified